The psycho-political Mobilization of the Mask in Dream on Monkey Mountain by Derek Walcott - Sayeed, Iffat (Journal of Research in Humanities, 2023)
Drawing upon the concept of metaphor as a linguistic expression for the emotional and intellectual response to a situation, this paper looks at the mask as the visual symbol of the psychic state of Makak and Lestrade. The focus of the dissertation is to show how the mask provides a symbolic and metaphorical sub-text that in combination with epigraphs prefaced in the play help to shape and intensify the fundamental conflicts that define the colonial and post colonial experiences of the protagonists of the play. With close reference to the text this paper looks at the mask as the most vital and viable element in the play that brings into relief the thematic strands embedded within the complex structure of the play. The paper also explores the manner in which the mask is transposed from one episode to another at eleven points in the play to lend cohesion and shape to the fluid structure of the play. Emphasising the centrality of the mask the link between the mask and the setting and progression of the plot of the play is studied.